Is risk good for saving? Message from the general equilibrium model - Yves Balasko; Enrique Kawamura (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
Popular press and some practitioners have warned against threats that buying risky assets pose on agents saving for retirement, children education and other uses. This paper shows that in a standard two-period general equilibrium model where some saver shave no risk-sharing motives, there exists a non-negligible set of economies (endowments) and equilibria at which every economic agent is better off if some risky assetsare added to riskless securities. Numerical examples actually show that the measure ofthe set of economies (endowments) with equilibrium allocations associated with trading risky assets that are Pareto superior to when there are only riskless assets can be larger than half the measure of the full set of economies.
Keywords: D14; D53; E21; D44; G11; G18; 330; general equilibrium; financial innovation; risky assets